Nonsurgical Management of a Patient with Hypopituitarism Secondary to Nonfunctioning Pituitary Macroadenoma: A Case Report - Martino Handoyo; Hermina Novida (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pituitary adenoma is a benign neoplasm of pituitary gland. Pituitary adenoma, particularly a macroadenoma,may produce mass effect symptoms by compressing surrounding tissues. Due to pituitary function as aneuroendocrine organ, pituitary adenoma may also cause multiple endocrine disturbances. The authors reportthe case of a 39-year-old male patient presenting with chronic headache and history of seizure. MRI imagingrevealed pituitary macroadenoma with optic chiasm compression. Further diagnostic workup indicatedsecondary hypogonadism and adrenal insufficiency. The patient was given hormone replacement therapyand was then advised for surgery, but the patient refused any surgical procedure. Subsequent follow-upswere somewhat difficult due to poor patient adherence. Nevertheless, appropriate management of pituitaryadenoma is needed to achieve optimal result.